Pengembangan Bahan Ajar Berbantu Website Digital pada Mata Pelajaran PAI Kelas II di MI/SD - Muhammad Syabrina; Ika Prima Susila; Wina Shella Andarista; Milda Anggraini; Mah Mudah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The development of digital website-based teaching materials aims to increase the effectiveness of learning Islamic Religious Education (PAI) in grade II MI / SD. This research uses the Service-Learning method, which connects education with community needs, as well as a technology-based development approach to create interactive and engaging teaching materials. The development process involved validation by material and design experts, followed by field trials with grade II students. The validation showed a very high level of feasibility, with an average rating above 90%. The pretest and posttest results showed significant improvement in students' understanding, proving that this learning media is effective. The teaching materials are systematically designed, including materials, evaluations, and multimedia elements such as videos and animations, which support a more engaging learning experience. The implementation of this teaching material changes the role of the teacher into a facilitator and increases students' active participation in learning. Web-based media provides flexibility and relevance to the digital era. With proven benefits, this teaching material is expected to be developed more widely to improve the overall quality of education.